2015
DOI: 10.1016/s1473-3099(14)71081-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of use of 13-valent pneumococcal conjugate vaccine in children on invasive pneumococcal disease in children and adults in the USA: analysis of multisite, population-based surveillance

Abstract: SUMMARY Background In 2000, 7-valent pneumococcal conjugate vaccine (PCV7) was introduced in the U.S. and resulted in dramatic reductions in invasive pneumococcal disease (IPD) and modest increases in non-PCV7-type IPD. In 2010, a 13-valent pneumococcal conjugate vaccine (PCV13) replaced PCV7 in the U.S. immunization schedule. We evaluated the effect of PCV13 use in children on IPD in children and adults in the U.S. Methods We used laboratory- and population-based data on incidence of IPD from CDC’s Emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
518
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 647 publications
(552 citation statements)
references
References 20 publications
27
518
2
5
Order By: Relevance
“…Among the most prevalent serotypes, 5 studies reported 22F ( 6.0%) 6,24,57,60,61 and 4 studies reported 11A ( 14.0%). 24,[61][62][63] Further, among the 4 studies reporting IPD-related pneumococcal illness, 6,24,57,58 serotypes 8 (range: 1.6-3.8%) and 12F (1.9-5.9%) were reported in all of them and 9N (3.8% and 4.2%) 6,58 and 10A (1.9% and 1.0%) 6,58 were reported in 2 studies. For non-IPD related carriage or illness, the most prevalent serotype was 11A in all 3 studies.…”
Section: Pneumococcal Serotype Distribution Among Adults Aged 65 Y Anmentioning
confidence: 94%
See 3 more Smart Citations
“…Among the most prevalent serotypes, 5 studies reported 22F ( 6.0%) 6,24,57,60,61 and 4 studies reported 11A ( 14.0%). 24,[61][62][63] Further, among the 4 studies reporting IPD-related pneumococcal illness, 6,24,57,58 serotypes 8 (range: 1.6-3.8%) and 12F (1.9-5.9%) were reported in all of them and 9N (3.8% and 4.2%) 6,58 and 10A (1.9% and 1.0%) 6,58 were reported in 2 studies. For non-IPD related carriage or illness, the most prevalent serotype was 11A in all 3 studies.…”
Section: Pneumococcal Serotype Distribution Among Adults Aged 65 Y Anmentioning
confidence: 94%
“…31,33,40,41,44 Prevalence of serotypes uniquely covered by PPV23 was reported in a total of 33 papers. Most often ranking in the top 3 among those serotypes in PPV23 but not in PCV13 for IPDrelated pneumococcal illness were serotypes 15B (or 15B/C) reported in 9 papers 6,[8][9][10]15,17,20,24,26 at up to 11.8% prevalent, 26 5 papers reporting serotype 22F ( 11.3%) 15 Prevalence of serotypes not covered by any pneumococcal vaccines (i.e., PCV13 or PPV23) was reported in a total of 34 papers. Most often ranking in the top 3 among nonvaccine serotypes in IPD-related pneumococcal illness were serotypes 15A reported in 4 papers at up to 6.5% prevalent, 8 15,17 and non-IPD (1.2-5.6%), 43,45,48 cases.…”
Section: Pneumococcal Serotype Distribution Among Children Aged Undermentioning
confidence: 99%
See 2 more Smart Citations
“…After ACIP recommended universal vaccination of children aged <2 years with 7-valent pneumococcal conjugate vaccine (PCV7) beginning in 2000, replaced by a 13-valent pneumococcal conjugate vaccine (PCV13) in 2010, 23 the U.S. and other countries experienced corresponding dramatic declines in invasive pneumococcal disease (IPD) caused by vaccine strains in vaccinated children. 24 However, the nationwide implementation of vaccine recommendations also significantly decreased the incidence of IPD among U.S. adults aged ≥65 years. 25 Streptococcus pneumoniae infections by serotypes in PCV13 in adults aged ≥65 years declined approximately 50% beginning in 2010 (when PCV13 replaced PCV7 in the routine childhood immunization schedule).…”
Section: Community Protectionmentioning
confidence: 99%